COMPARATIVE ANALYSIS OF MODEL PROGRAMS OF THE INTEGRATED COURSE "HEALTH, SAFETY AND WELL-BEING" 5-6 GRADES - Zaplatynskyi, Vasyl (Educological discourse, 2022)
The article is devoted to a comparative analysis of five model curricula of the integrated course "health, safety and well-being" for grades 5-6 for schools of general secondary education of different groups of authors. These programs were recommended in 2021 by the Ministry of Education and Science of Ukraine. The expediency of conducting a study of model programs is due to the need for teachers to freely choose one basic model program, which will become the basis for writing the curriculum of an school. The article presents selected research results, which include a comparative analysis of the volume and structure of model programs. The presented results include an analysis of the features of the programs, a comparison of the content of the main part, namely, the proposed topics, types of learning activities and expected learning outcomes. The presented results cover only issues related to transport safety in programs, as an example of one aspect of a general study that includes a comparison of all relevant topics that are provided for by the State Standard. The presented research results allow us to reasonably and balancedly choose a model program that will best fit the characteristics of the educational institution, including internal and external social, natural and man-made factors. In addition, the presented analysis allows you to get acquainted with the interesting proposals of various authors' teams on topics and types of educational activities that can be used to write your own program and its implementation.